Main Financial Regulators: Comparative Analysis of Federal Reserve and Euro System - Malyshko, O.V.; German, K.A. (Економічний вісник Донбасу, 2013)
This article contains a systematic comparison of the Eurosystem and the US Federal Reserve System as the major economic regulators. Comparative analysis of these two systems was performed. Monetary policy essence and its effects were described as well as monetary aggregates.